Defining a role for non-satellite stem cells in the regulation of muscle repair following exercise - Boppart, Marni D.; De Lisio, Michael; Zou, Kai; Huntsman, Heather D. (Frontiers in Physiology, 2013)
Skeletal muscle repair is essential for effective remodeling, tissue maintenance, and initiation of beneficial adaptations post-eccentric exercise. A series of well characterized events, such as recruitment of immune cells and activation of satellite cells, constitute the basis for muscle regeneration. However, details regarding the fine-tuned regulation of this process in response to different types of injury are open for investigation. Muscle-resident non-myogenic, non-satellite stem cells expressing conventional mesenchymal stem cell (MSC) markers, have the potential to significantly contribute to regeneration given the role for bone marrow-derived MSCs in whole body tissue repair in response to injury and disease. The purpose of this mini-review is to highlight a regulatory role for non-satellite stem cells in the process of skeletal muscle healing post-eccentric exercise. The non-myogenic, non-satellite stem cell fraction will be defined, its role in tissue repair will be briefly reviewed, and recent studies demonstrating a contribution to eccentric exercise-induced regeneration will be presented.